Structural Response of a Reinforced Concrete Building to Earthquake Excitation: A Nonlinear Time-History Analysis Case Study in Palu, Indonesia - Indah N. Afiah; Mohammad J. Rahman; Mentari S. Sitorus; Zulfadli Ibrahim (Journal of Civil Engineering, 2025)
Palu is one of the regions with high seismicity due to its location directly on the Palu-Koro Fault, the longest active fault in Indonesia. A post-earthquake structural response evaluation was conducted on a reinforced concrete office building in Palu, Indonesia, using nonlinear time-history analysis to assess its performance under seven recorded ground motions. This evaluation serves as a reference for determining the structural functionality, safety against collapse, and the need for structural reinforcement due to earthquake loads. The primary focus was to assess the serviceability limit state and ultimate limit state in accordance with SNI 1726:2019 and to determine the performance level category based on ATC-40. Modeling was conducted using ETABS software with input from earthquake accelerograms of the Superstition Hills, San Fernando, Kobe, Loma Prieta, El Centro, Caldiran, and Manjil earthquakes. The results show significant variations among the earthquake scenarios. The highest displacement and drift values occurred in the Y-direction due to the El Centro earthquake, while the lowest values were observed in the X-direction during the Caldiran earthquake. Only the Caldiran earthquake met the limit criteria in both directions. Based on ATC-40, three earthquakes (Caldiran, Loma Prieta, and San Fernando) reached the Immediate Occupancy (IO) and Life Safety (LS) levels. In comparison, the other four earthquakes showed levels exceeding Collapse Prevention (>CP), indicating potential building failure and high hazard risks. Therefore, further evaluation and retrofit recommendations are necessary to enhance the structure's capacity and stiffness, thereby achieving the desired performance level in all earthquake scenarios.